Vegetation dynamics drive segregation by body size in Galapagos tortoises migrating across altitudinal gradients. (21st November 2012) - Blake, Stephen; Yackulic, Charles B.; Cabrera, Fredy; Tapia, Washington; Gibbs, James P.; Kümmeth, Franz; Wikelski, Martin; Fryxell, John
Summary Seasonal migration has evolved in many taxa as a response to predictable spatial and temporal variation in the environment. Individual traits, physiology and social state interact with environmental factors to increase the complexity of migratory systems. Despite a huge body of research, the ultimate causes of migration remain unclear. A relatively simple, tractable system – giant tortoises on Santa Cruz Island, Galapagos, was studied to elucidate the roles of environmental variation and individual traits in a partial migratory system. Specifically, we asked: (i) do Galapagos tortoises undergo long‐distance seasonal migrations? (ii) is tortoise migration ultimately driven by gradients in forage quality or temperature; and (iii) how do sex and body size influence migration patterns? We recorded the daily locations of 17 GPS‐tagged tortoises and walked a monthly survey along the altitudinal gradient to characterize the movements and distribution of tortoises of different sizes and sexes. Monthly temperature and rainfall data were obtained from weather stations deployed at various altitudes, and the Normalized Difference Vegetation Index was used as a proxy for forage quality. Analyses using net displacement or daily movement characteristics did not agree on assigning individuals as either migratory or non‐migratory; however, both methods suggested that some individuals were migratory. Adult tortoises of both sexes move up and down an altitudinal gradient in response to changes in vegetation dynamics, not temperature. The largest tagged individuals all moved, whereas only some mid‐sized individuals moved, and the smallest individuals never left lowland areas. The timing of movements varied with body size: large individuals moved upward (as lowland forage quality declined) earlier in the year than did mid‐sized individuals, while the timing of downward movements was unrelated to body size and occurred as lowland vegetation productivity peaked. Giant tortoises are unlikely candidates for forage‐driven migration as they are well buffered against environmental fluctuations by large body size and a slow metabolism. Notably the largest, and presumably most dominant, individuals were most likely to migrate. This characteristic and the lack of sex‐based differences in movement behaviour distinguish Galapagos tortoise movement from previously described partial migratory systems.